MEKANISME DIGITALISASI TERHADAP KOLEKSI LANGKA DI UPT PERPUSTAKAAN PROKLAMATOR BUNG KARNO BLITAR - Winastwan, Rheza Ega (Jurnal El-Pustaka, 2020)
The proclamator Bung Karno Library has many important collection of the history of  Soekarno. In order to maintain and preserve collections of historical value. The purpose of this research to provide an overview of the process of digitizing and distributing the results of digitization. This research is a qualitative study with a descriptive approach. Data collection was carried out in three ways, namely participant observation, interviews, and documentation. The results showed that the digitization process consisted of taking photos of rare collections, editing photos using the Photoshop, entering photos into the flipbook maker, and entering the digitizing files into a CD. The distribution process is done by uploading it to the library website and serving in audio visual services. With the digitization of rare collections, the Bung Karno Library has contributed to preserving rare collections that cannot be served conventionally.